Minicircle‐based GCP‐2 ex vivo gene therapy enhanced the reepithelialization and angiogenic capacity. (18th May 2020) - Han, Ju Hye; Han, Seongho; Jeong, In Sil; Cheon, Sae Hee; Kim, Sung‐Whan
Abstract: Recently, minicircle (MC)‐based cell therapy has been emerging as a novel technology for nonviral genetic modification. In this study, we investigated the characteristics of granulocyte chemotactic protein‐2 (GCP‐2)‐overexpressing fibroblasts (GCP‐2/MC) using MC microporation technology, as well as its therapeutic mechanism in wound healing. GCP‐2 parent plasmid and MC containing GCP‐2 were generated. Human dermal fibroblasts (HDF) were transfected with MC containing GCP‐2. Quantitative reverse transcription polymerase chain reaction (qRT‐PCR), scratch wound assay, and in vivo wound healing assay were performed. Gene and protein expression analysis revealed that GCP‐2/MC highly expressed epithelialization growth factor, epidermal growth factor (EGF), chemokines, GCP‐2, interleukin (IL)‐8, as well as wound healing‐associated genes such as insulin growth factor (IGF)‐1 and hepatocyte growth factor (HGF). An in vitro scratch wound closure and matrigel tube formation assays demonstrated that the culture medium derived from GCP‐2/MC substantially accelerated the wound closure and matrigel network formation. Wounds in nude mice were created by skin excisions followed by injections of GCP‐2/MC. Results showed high cell survival potential and that GCP‐2/MC transplantation highly accelerated skin wound closure by increasing reepithelialization, capillary density, and enhancing angiogenic factors, suggesting direct benefits for cutaneous closure. Taken together, these data suggest that MC‐based GCP‐2 overexpression could be a promising alternative strategy for promoting wound healing.